Analysis of effective pore pressure in asphalt pavement based on computational fluid dynamics calculation. (February 2017) - Guo, Xuedong; Sun, Mingzhi; Dai, Wenting
A micromechanical model was established based on the fluid dynamics theory. This model could be used to calculate several kinds of data when the asphalt pavement under the influence of traffic loading is in water-saturated condition. The results showed that the maximum pressure inside the effective pore was located at the junction between exit slits and the pore wall. There was a positive correlation between the pressure and the vehicle speed. Therefore, the repeated traffic loading could cause emulsification, shift and even peeling of the asphalt membrane. Moreover, the bigger size of the exit slit is, the higher velocity of the fluid has. The high velocity flow keeps scouring both the exit slit and the lower boundary of pore wall. It will cause a bigger slit. Pressure distribution inside the effective pore is related to the number of the exit slit which connect with the pore. More exit slits means bigger pressure inside the effective pore. In addition, if asphalt membranes at exit slits have micro-cracking, the cumulative damage could appear easily and asphalt membranes could be peeled easily. Finally, a test was conducted so as to obtain the bonding strength and adhesion strength between asphalt and aggregate. Then, we can get accurate damage form and position during the scour process by comparing the numerical simulation results with experiment results.